(untitled) (AYUSHDHARA, 2023)
Stress is a state of mental strain for a specific person experiencing issues with their social and environmental well-being, which can result in a variety of illnesses. The important phage is when a person is young since this is when their life is going through a lot of change. They are expected to be members of the social elite. Therefore, kids should improve their stress-management skills to live healthy lives after they join the society. Comparing stress to Avasad in Ayurveda (Vatanatamaja vikaras). It’s regarded as being among the Manasik Rogas. Ayurveda deals with the mind and body of human beings. Only the conventional system of medicine helps to maintain health in the healthy while also treating the sick. The Ahar vihar, Aushad, and Sanshodhan principles of Ayurveda’s therapy are included. Two types of medication internal and external are described in the classical texts of Ayurveda. Many herbal and herbal-mineral concoctions are referred to be "Medhya medicines" in internal medicine. Like Mandukparni Brahmi, Vacha, Shankhpushpi, Giloy, Jyotismati, Ashwagandha, Tagar, etc., the majority of them have been scientifically and therapeutically shown to be effective stress relievers. In terms of external medicine, Panchakarma techniques like Shirodhara are also described. Shirodhara treatment is frequently used to treat psychological disorders. Although Shirodhara’s clinical effectiveness has been established, its mode of action is complicated. Shirodhara aids in soothing the anxious mind and relaxing the entire body because the body, mind, and spirit are all interconnected. Shirodhara’s therapeutic effectiveness has been established, however, its mode of action is complicated. Since the body, mind, and spirit are all intertwined, Shirodhara helps to quiet a busy mind and rest the entire body.